NIR-II fluorescence imaging using indocyanine green nanoparticles - Bhavane, Rohan (Sci Rep, 2018)
Fluorescence imaging in the second near-infrared window (NIR-II) holds promise for real-time deep tissue imaging. In this work, we investigated the NIR-II fluorescence properties of a liposomal formulation of indocyanine green (ICG), a FDA-approved dye that was recently shown to exhibit NIR-II fluorescence. Fluorescence spectra of liposomal-ICG were collected in phosphate-buffered saline (PBS) and plasma. Imaging studies in an Intralipid(®) phantom were performed to determine penetration depth. In vivo imaging studies were performed to test real-time visualization of vascular structures in the hind limb and intracranial regions. Free ICG, NIR-I imaging, and cross-sectional imaging modalities (MRI and CT) were used as comparators. Fluorescence spectra demonstrated the strong NIR-II fluorescence of liposomal-ICG, similar to free ICG in plasma. In vitro studies demonstrated superior performance of liposomal-ICG over free ICG for NIR-II imaging of deep (≥4 mm) vascular mimicking structures. In vivo, NIR-II fluorescence imaging using liposomal-ICG resulted in significantly (p < 0.05) higher contrast-to-noise ratio compared to free ICG for extended periods of time, allowing visualization of hind limb and intracranial vasculature for up to 4 hours post-injection. In vivo comparisons demonstrated higher vessel conspicuity with liposomal-ICG-enhanced NIR-II imaging compared to NIR-I imaging.